Necrotic cell death - Vandenabeele, Peter; Shen, Han-Ming (Cell Death in Biology and Diseases, 2014)
This essential volume in the Cell Death in Biology and Diseases series presents comprehensive coverage of necrosis from recognized experts at leading academic and medical institutions around the world, thus keeping pace with the emerging research interest in necrosis. Starting with discussion of basic concepts and the molecular mechanisms of necrosis, this book looks first at the several forms of necrotic cell death that have been identified, including necroptosis, autophagic cell death, and PARP-mediated cell death.  As necrotic cell death is increasingly known to play a critical role in many physiological processes, the next chapters discuss its effect on metabolism, inflammation, immunity, and development. Necrotic cell death is closely implicated in human diseases like cancer so the next chapters examine its relevance to human diseases, and final chapters cover methodologies for measuring necrosis.